2022
DOI: 10.18280/rcma.320303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graphite Addition on Aluminum Hybrid Matrix Composite by Powder Metallurgy Method

Abstract: The requirement for optimal strength and lightweight materials is a challenge in today's automotive industry. In this study, the synthesis of aluminum matrix hybrid composites containing magnesium and copper with the addition of graphite 0, 1, 3, and 5% by volume was carried out using powder metallurgy techniques and investigated the effect of the treatment given. The investigation of composite properties was carried out by testing density, porosity, hardness, wear rate, XRD, and SEM investigations integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
2
0
3
Order By: Relevance
“…Terdapat berbagai metode dalam pembuatan komposit, seperti stir casting, powder metallurgy, compo casting, friction stir casting, roll bonding dan lain-lain [1]. Namun demikian metode powder metallurgy atau metalurgi serbuk memiliki beberapa keuntungan dibandingkan dengan proses lainnya, sehingga pembuatan komposit dengan teknologi metalurgi serbuk ini semakin dikembangkan pada akhir-akhir ini [2].…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Terdapat berbagai metode dalam pembuatan komposit, seperti stir casting, powder metallurgy, compo casting, friction stir casting, roll bonding dan lain-lain [1]. Namun demikian metode powder metallurgy atau metalurgi serbuk memiliki beberapa keuntungan dibandingkan dengan proses lainnya, sehingga pembuatan komposit dengan teknologi metalurgi serbuk ini semakin dikembangkan pada akhir-akhir ini [2].…”
Section: Pendahuluanunclassified
“…Beberapa keuntungan pembuatan komposit dengan metode metalurgi serbuk adalah energi proses yang rendah [3], lebih ekonomis karena lebih sedikit bahan yang hilang atau sebagian besar bahan baku menjadi produk jadi [4]. kecepatan produksi tinggi karena dapat memproduksi produk secara massal, dapat memproduksi produk dengan bentuk yang rumit dengan ukuran kecil, serta mudah dalam mengontrol parameter proses produk serta mampu memproduksi produk dengan dimensi yang lebih akurat [1]. Proses utama pada teknologi metalurgi serbuk ada tiga tahapan yaitu tahapan proses pencampuran serbuk matrik dengan serbuk penguat, tahapan proses penekanan atau kompaksi dan tahapan proses sintering [5].…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Polymer-based composites are intended for performance, durability, and resistance to applied stress and temperature [1]. Resin polymer composites reinforced with natural or synthetic fibers were used in the 30s of this century [3]. Due to the increasing economic requirements, there was a need for natural materials to replace synthetic materials such as jute and others to support polymeric materials, so their residues were used to support these materials [4].…”
Section: Introductionmentioning
confidence: 99%
“…Shahid et al [28] investigated the porosity, density, wear and hardness of aluminium matrix hybrid composites with addition of varying amounts of graphite. The conclusions of the study are the composition with 5% volume of graphite showed better performance in terms of improved mechanical properties.…”
Section: Introductionmentioning
confidence: 99%